2017
DOI: 10.1007/s10509-017-3034-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of events with metric-to-decahectometric type II radio bursts associated with CMEs and flares in relation to SEP events

Abstract: A gradual solar energetic particle (SEP) event is thought to happen when particles are accelerated at a shock due to a fast coronal mass ejection (CME). To quantify what kind of solar eruptions can result in such SEP events, we have conducted detailed investigations on the characteristics of CMEs, solar flares and metric-to-decahectometric wavelength type II radio bursts (herein after m-to-DH type II bursts) for SEP-associated and non-SEP-associated events, observed during the period of 1997-2012. Interestingl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
0
9
2
Order By: Relevance
“…The average height of Category 1 events is in fairly good agreement with the average shock formation heights found by Gopalswamy et al (2013) for 32 CMEs associated with metric type II bursts. On the other hand, the shock formation heights of Category 1 and 2 events are slightly lower than those reported by Prakash et al (2017) for metric type II bursts (1.58 R ) and for DH type II bursts (3.54 R ) associated with SEP events. Prakash et al (2017) determined the shock formation heights by back extrapolation of the CME heights assuming a constant CME speed.…”
Section: Proton Release Heightscontrasting
confidence: 65%
See 1 more Smart Citation
“…The average height of Category 1 events is in fairly good agreement with the average shock formation heights found by Gopalswamy et al (2013) for 32 CMEs associated with metric type II bursts. On the other hand, the shock formation heights of Category 1 and 2 events are slightly lower than those reported by Prakash et al (2017) for metric type II bursts (1.58 R ) and for DH type II bursts (3.54 R ) associated with SEP events. Prakash et al (2017) determined the shock formation heights by back extrapolation of the CME heights assuming a constant CME speed.…”
Section: Proton Release Heightscontrasting
confidence: 65%
“…On the other hand, the shock formation heights of Category 1 and 2 events are slightly lower than those reported by Prakash et al (2017) for metric type II bursts (1.58 R ) and for DH type II bursts (3.54 R ) associated with SEP events. Prakash et al (2017) determined the shock formation heights by back extrapolation of the CME heights assuming a constant CME speed. Figure 8a showed a clear dependence of the proton intensity rise rate on the difference between the proton release time and type III onset time.…”
Section: Proton Release Heightscontrasting
confidence: 65%
“…This corresponds to a plasma frequency in the low corona of 1.6 GHz, and second harmonic of 3.2 GHz. However, most solar CMEs do not form shocks low in the corona, accelerating with height as Alfvén speed declines with height, enabling them to form shocks at heights of ∼ 1.3−2R * Prakash et al 2017). For now, to estimate plausible start frequencies for stellar Type II bursts, we consider the case where a shock forms at r = 2R * .…”
Section: Choice Of Frequency Bandsmentioning
confidence: 99%
“…Scattering of data points in this plot indicated the involvement of other factors in the particle acceleration [38] [25] [13] [53]. Later many authors found that the peak intensity of SEPs correlated with both speed and width of the associated CMEs [36] [66] [25] [59] [15] [63]. Significant number of authors pointed out that duration of the solar flares is important parameter to predict the space weather events [9] [40] [69].…”
Section: Introductionmentioning
confidence: 99%